2019
DOI: 10.1177/1077546319889846
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear numerical and experimental study on the second-order torsional and lateral vibration of driveline system connected by cardan joint

Abstract: In this article, a nonlinear dynamic model with five degrees-of-freedom for a four-wheel-drive vehicle driveline connected by a cardan joint, including dynamic intersection angle, nonconstant velocity, and additional moment caused by the cardan joint, is established by using the Lagrange method to analyze the driveline coupling vibration in both torsional and lateral directions. High-order Runge–Kutta algorithm is applied to solve the differential equations and to calculate transient responses of the driveline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
0
16
1
3
Order By: Relevance
“…The amplitude of each frequency component varies nonlinearly and, at a certain speed, there is a continuous spectrum component evident in the three-dimensional spectrum. Contrary to the results in [5], the vibration response demonstrated that the second-order vibration and noise generated by the Cardan joint can be decreased effectively by considering the effects of the fluid forces. In summary, nonlinear fluid forces have an important influence on the stable operation and dynamic characteristics of the driveshaft system.…”
Section: Influence Of Fluid Forces On the Vibration Response Of The Rubbing Coupled Systemcontrasting
confidence: 89%
See 1 more Smart Citation
“…The amplitude of each frequency component varies nonlinearly and, at a certain speed, there is a continuous spectrum component evident in the three-dimensional spectrum. Contrary to the results in [5], the vibration response demonstrated that the second-order vibration and noise generated by the Cardan joint can be decreased effectively by considering the effects of the fluid forces. In summary, nonlinear fluid forces have an important influence on the stable operation and dynamic characteristics of the driveshaft system.…”
Section: Influence Of Fluid Forces On the Vibration Response Of The Rubbing Coupled Systemcontrasting
confidence: 89%
“…In this regard, the authors performed the Lagrange formalism to analyse the vibration of the driveline coupling in the torsional and lateral directions. Their study showed that the second-order vibration and noise are generated by the Cardan joint, and the noise can be decreased effectively by reducing the intersection angle of the Cardan joint [5]. Several studies of flexible Cardan shaft instabilities have been conducted to shed more light on the dynamic behaviour of the lateral and torsional vibration caused by the Cardan joint on a vehicle's driveline, except for fault diagnosis in the fluid domain.…”
Section: Introductionmentioning
confidence: 99%
“…Дослідженню та конструюванню шарнірів нерівних кутових швидкостей присвячена значна кількість робіт. В них розглядаються питання, пов'язані зі структурою, геометричними і кінематичними параметрами універсального шарніра [1][2][3][4], присвячені дослідженню його динаміки [4][5][6][7][8][9][10][11][12][13], надійності [13,14], а також питання, які орієнтовані на конструювання та розрахунок карданних передач [15,16]. Незважаючи на різну направленість робіт, практично кожне дослідження шарніра передбачає кінематичний аналіз і грунтуєть-ся на його результатах.…”
Section: аналіз публікаційunclassified
“…To ensure a relative steady angular velocity, cardan joints are coupled in pairs, composing the so-called double cardan joint. In AWD cars, this transmission is subjected to the maximum motor torque, high dynamic loadings [ 2 , 4 ], and high torsional and lateral vibrations [ 5 , 6 ]. There are various AWD driveline configurations, presenting permanently engaged cardan joints or engaged “on-demand”, as in off-road hikes.…”
Section: Introductionmentioning
confidence: 99%